The relevance of having internship programs for fifth-year students from the Bachelor of Arts in Modern Languages at the Foreign Language Department of the University of El Salvador during the Year 2015. - Chavarría Rico, Claudia Eunice
In El Salvador, the learning of English and French as foreign languages have increased more and more in the last years. English is the official language in a large number of countries and French can help tremendously with a career prospect, college education and personal experience; that is why these languages have become very important for many students. When the students analyze those benefits and even more they decide to learn either English, French or even both, they work hard and they gain the knowledge that institutions provide to learn and apply those languages; however, at the moment of the facing a real job environment, students who have graduated from the B.A.in Modern Languages face many obstacles; one of them is that the students feel very unprepared to face or to employ their knowledge in a work space. This project has been focused on how relevant it could be to have an Internship program for fifth-year students from the Bachelor of Arts in Modern Languages at the Foreign Languages Department of the University of El Salvador. Furthermore, it explores how beneficial it could be for the students of this major, since even though the learning process is very good in the University of El Salvador, they need to have some practices to improve the communication skill before graduating in order to face the environment of a real job with confidence. The research is intended to present the benefits that an Internship project could provide and also the acceptance of students if that would happen for the fifth-year students from the Major of Modern Languages of the University of El Salvador.